Voting system / Meor Muhammad Zulfadli Saad … [et al.] - Saad, Meor Muhammad Zulfadli; Ab Rahim, Abu Talib; Muhalith@Muhalis, Mohd Amir Fared; A.Rahim, Muhammad Amirul Ardy; Mohd Ariffin, Mohamad Azwan; Zulkifli, Zarul Asyraf; Abd Hamid, Abdullah Bukhary (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Voting system is system voting MPP using SMS. Vote MPP use SMS invented to facilitate students because student can vote MPP from anywhere they well off without time constraint. This system use GSM modem which functions to received and give by SMS bulk in at one time. Its communed is visual basic software. This system have feature 'friendly student' because almost all students have mobile phone, so is extremely unlikely if they do not vote in the election university. Besides that, student also should not take long time to vote. This system will facilitate and save a cost, so overall it can reduce money and energy. Apart from in university, this system also can be applied in outside world in any related fields.